LANGUAGE STYLE BETWEEN PRESENTERS IN TALK SHOW - Riza Mulyani; Hamzah Hamzah; Rusdi Noor Rosa (Universitas Negeri Padang, 2018)
This study aims to, 1) show the similarities and differences between language style used by Jimmy Kimmel and Wendy Williams in the level of ideational metafunction, 2) show the similarities and different language styles used by Jimmy Kimmel and Wendy Williams in the level of interpersonal metafunction,3) show the similarities and differences of language styles used by Jimmy Kimmel and Wendy Williams in the level of textual metafunction. The objects of this research are eight talk show videos. Four videos from man presenter and four videos from a woman presenter of talk show. The result of this research show four similarities and three differences between two speakers in level Ideational metafunction. In Interpersonal metafunction there are six similarities and three differences. Then, there are two similarities and three differences between both speakers in textual metafunction. The conclusion of this study there are more similarities rather then differencies, and the differences in style are affected by different gender which are pepresented through speech and lead to the different ways of producing and selection of word in the three level of metafunction.